THE ROLE OF KNOWLEDGE-ORIENTED LEADERSHIP AND CUSTOMER KNOWLEDGE MANAGEMENT IN DRIVING INNOVATION IN SMES: A CONCEPTUAL FRAMEWORK - Sarah Fadilla; Adisthy Shabrina Nurqamarani; Sarah Anistia (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
In the era of dynamic and changing behaviour, innovation has become a crucial factor for Small and Medium Enterprises (SMEs) to grow, adapt, and survive. Despite their importance, SMEs are often perceived as vulnerable due to limited financial capital and human resource capabilities. However, adopting knowledge-oriented leadership (KOL) and leveraging customer knowledge management (CKM) can offer a strategic pathway to overcome these limitations. This paper proposes a conceptual framework that examines the role of knowledge-oriented leadership (KOL) and customer knowledge management (CKM) in promoting innovation within small and medium-sized enterprises (SMEs). Drawing on the knowledge-based view of the firm, the framework posits that leaders who emphasize knowledge sharing, learning, and strategic knowledge utilization can effectively harness customer knowledge to drive innovation outcomes. When the firm systematically acquires, shares, and applies customer knowledge, it can act as a valuable source of insight in developing new products, improving service, and business model innovation. This study contributes to the literature by combining KOL and CKM perspectives and offers a theoretical framework for further empirical validation. The framework also acts as a strategic manual for SME practitioners who want to use knowledge-centric methods to improve their capacity for innovation.